Project Based Learning Pada Mata kuliah Kewirausahaan Dalam Membentuk Kemandirian Mahasiswa Dalam Berwirausaha: Project Based Learning Pada Mata kuliah Kewirausahaan Dalam Membentuk Kemandirian Mahasiswa Dalam Berwirausaha - Mohamad Irsyad (Improvement: Jurnal Ilmiah untuk Peningkatan Mutu Manajemen Pendidikan, 2019)
This article aims to find ou how project based learning in entrepreneurship courses applied in IAIN Surakarta in shaping students independence in entrepreneurship. This study uses a Classroom Action Research method. This research is describing data, facts and circumstances that occur in the field. The object of this research is 38 students the Arabic Language and Literature, Faculty of Adab and Language IAIN Surakarta. Data collection is done by instruments of student performance and learning outcomes. Performance instruments by assessing student activity in carrying out assignments, conducting business consultations, presenting products, and reporting results. Data from observations were analyzed using qualitative descriptive techniques. In this study it was produced that the application of the project-based learning model could create student independence in producing a product that would ultimately be able to make students economically independent. However, the researchers hope that further research will not only discuss how to apply it, and success in producing products, but also can discuss the business continuity that has been born and create by students.